Differences In Nutrient Content In Peat Land And Permanent Production Forest Area In Sei Paham Village, Sei Kepayang District, Asahan District - Fauzi Agus Suryandi; Hilwa Walida; Khairul Rizal; Badrul Ainy Dalimunte (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
Peat soils are classified as marginal soils and are prone to disturbance, so efforts to increase land productivity must be followed by efforts to prevent ecosystem damage. This study aims to analyze differences in nutrient content in peat land and permanent production forest areas in Sei Paham Village, Sei Kepayang District, Asahan District . Taking 5 soil sample points was carried out using a proposive random sampling method . The soil sample is then placed in a sterile plastic bag and immediately taken to the laboratory for analysis. The parameters of the soil analysis carried out included pH , C-total, N, P, K, Ca, Na, Mg, CEC and C/N. The results showed that in permanent production forest, the nutrient content was higher than peatland in all parameters of soil chemical analysis.